Multifidus fat infiltration negatively influences the postoperative outcomes in lumbar disc herniation following transforaminal approach percutaneous endoscopic lumbar discectomy - Kai Sun; Renjie Qin; Wenzhuo Wang; Genlong Jiao; Guodong Sun; Guoliang Chen; Jun Li (European Journal of Medical Research)
Abstract Purpose This study aims to investigate the influence of multifidus muscle fat infiltration on clinical outcomes in lumbar disc herniation (LDH) undergoing percutaneous endoscopic lumbar discectomy (PELD). Methods A retrospective analysis was conducted on 224 patients who underwent lateral PELD, with complete one-year follow-up data. Patients were divided into two groups based on preoperative MRI evaluation of L4 multifidus muscle fat infiltration: a mild group (< 25%) and a severe group (≥ 25%). Baseline characteristics and postoperative outcomes were recorded and compared. Results At the final follow-up, significant improvements in VAS scores for back and leg pain, ODI scores, and EQ-5D scores were observed in both groups. There were no statistically significant differences in preoperative VAS scores for back and leg pain, ODI scores, and EQ-5D scores between the two groups. However, significant differences were found in VAS scores for back pain, ODI scores, and EQ-5D scores at 3, 6, and 12 months postoperatively (P < 0.05), while no significant difference was noted in VAS scores for leg pain during follow-up. The total recurrence rate was 6.7% (15 out of 224 cases), with 12 cases in the severe group and 3 cases in the mild group, showing a statistically significant difference (P < 0.05). Conclusion The effectiveness of postoperative PELD in patients with LDH is impacted by severe multifidus muscle fat infiltration. Multifidus muscle fat infiltration represents a risk factor for recurrent LDH after PELD.